Strategi Kolonial Belanda Dalam Menaklukkan Kerajaan Aceh Darussalam (Jurnal Adabiya, 2020)
The Kingdom of Aceh Darussalam was proclaimed by Sultan Ali Mughayat Syah in 1514 AD The sultans succeeded in making this kingdom as a great, powerful and influential kingdom in Sumatra, Southeast Asia and the world. This region is famous not only of the world’s high export products, but its strategic locationserves as the foundation for Western imperialists to respect the sovereignty of the Kingdom of Aceh Darussalam and seek to establish political and economic cooperation with it, such as Portuguese, English and Dutch. The Netherlands has cooperated with Aceh, though not always running smoothly. Political and economic changes in Europe affected the colonies of the Indies. The Netherlands not only trade with Aceh, but conquered it. Various reasons and strategies are sought and organized systematically. First dragged England into the London Tractat as an entrance to instill its influence in Sumatra, including Aceh. Although the Dutch agreed that they would not disturb the sovereignty of Aceh. Then the Dutch also urged the British to make a treaty Soematra Tractat. Itaims to make Dutch more able to master Aceh. With this last treaty the Dutch bravely disrupted the sovereignty of Aceh, beginning with the provocation and subjugation of Aceh’s regional domains in Sumatra, such as Barus, Siak and Deli, and Trumon and Singkil in Aceh itself. Last pressed the sultan of Aceh and pounded the center of the Kingdom of Aceh.
Keywords: Strategy; Dutch Colonial; Conquest of the Kingdom of Aceh Darussalam